The Teachers of Suntisart Wittaya School’s Perception Toward English Students of UMMU in Joining Apprentice Program in Thailand - Faujia Umasugi; Musaif Nasruin (EDU Journal - English Department of UMMU Journal, 2021)
Every teacher has a different perception of student who take apprentice program. Each will express their opinion based on what they observe, starting from what they saw and heard directly. For example, the appearance of apprentices, their behavior, and the way they interact with students at school and the whole community around the school. The primarypurpose of this research is to determine the various perceptions ofthe teachersSuntisartWittaya School’s on the competence of International student of apprentice in the English DepartmentProgram of Muhammadiyah University of North Maluku (UMMU). This research was conducted at SuntisartWittaya School Kabang District, Yala Province, Southern Thailand in 2019-2020. The Sample of this study was 20 teachers in school who had observed an apprentice for 5 months in Thailand. The method used in this research is qualitative method. To analyze qualitatively from the data, the interviewee's responses or opinions for each question were transcribed. After that, the stages of the analysis were reviewed from themes related to the study objectives. Data from questionnaire it shows that the total mean score in the perception of teachers is4,45 and this is a high level. From interview data also shows that the teachers of Suntisart Wittaya School’s are very happy, welcome, and they also need the Apprentice Program that could be continued in every year.